THE EFFECT OF STUDYING PROBLEM BASED LEARNING (PBL) TO THE X GRADE OF SMA NEGERI 6 SURAKARTA STUDENTS CRITICAL THINGKING ABILITY IN ACADEMIC YEAR 2012/2013 - Joko Ariyanto, Lia Ullynuha, Baskoro Adi P (P Biologi FKIP UNS Surakarta, 2015)
This research is to know the effect of studying Problem Based Learning (PBL) to tenth grade of SMA Negeri 6 Surakarta students critical thingking ability in academic year 2012/2013..This research include on Quasy Experiment with the research design posttest only non equivalent group design. This research applies Problem Based Learning (PBL) to the experiment group and variative communication method learning to control group. The population research is the whole of tenth students of SMA 6 Surakarta year 2012/2013. The withdrawal sample technic is sampling cluster and is taken two clasess the experiment group and control group. The data collection technic uses test technic to know the environment pollution and the measure the students? critical ability, the school documentation as the first ability used to test the balace, and observation sheet to see the doing activity in the form of: the students? action, ability, and attitude. Hypothesis test uses T-test with SPSS 16 program.This research results is to show that through application learning Problem Based Learning, students participate actively in the learning process. The hypothesis test results the conclusion test (sig) 0,05 until the HO is refused. This means that the average result critical ability between control class and experiment class are different. The pronouncement is also supported descriptively that is form the average value of critical ability in the amount of 76.14862 for the experiment class and 83.24593 for the control class.This research concludes that Problem Based Learning affects to the tenth students' critical ability of SMAN 6 Surakarta year 2012/2013.